2022
DOI: 10.1002/anie.202117809
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Hydrogenation of Furfural in Aqueous Acetic Acid Media with Enhanced 2‐Methylfuran Selectivity Using CuPd Bimetallic Catalysts

Abstract: Herein, we report a series of CuPd catalysts for electrochemical hydrogenation (ECH) of furfural to 2‐methylfuran (MF or FurCH3 where Fur=furyl) in aqueous 0.1 M acetic acid (pH 2.9). The highest faradaic efficiency (FE) for MF reached 75 % at −0.58 V vs. reversible hydrogen electrode with an average partial current density of 4.5 mA cm−2. In situ surface‐enhanced Raman spectroscopic and kinetic isotopic experiments suggested that electrogenerated adsorbed hydrogen (Hads) was involved in the reaction and incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 64 publications
4
66
0
Order By: Relevance
“…As shown in Figure d, there emerge two absorbance peaks at 1482 and 1231 cm –1 which can be attributed to the adsorption of O 2 (O 2,ad ) and HOO* (OOH ad ), respectively, according to previous reports. , A similar OOH ad peak with increasing strength can be observed for Co–N SAC Mm (Figure S33) relative to Co–N SAC Dp . The relatively strong OOH ad peak on the Co–N SAC Mm may be related to the higher coverage of HOO* considering the similar measurement procedure of in situ ATR–SEIRAS. Summarizing the abovementioned results, we use the experimental evidence to verify the DFT calculation results that the Co–N SAC Dp with pyrrole-type CoN 4 favors the H 2 O 2 production as compared to the Co–N SAC Mm (pyridine-type CoN 4 ).…”
Section: Resultsmentioning
confidence: 78%
“…As shown in Figure d, there emerge two absorbance peaks at 1482 and 1231 cm –1 which can be attributed to the adsorption of O 2 (O 2,ad ) and HOO* (OOH ad ), respectively, according to previous reports. , A similar OOH ad peak with increasing strength can be observed for Co–N SAC Mm (Figure S33) relative to Co–N SAC Dp . The relatively strong OOH ad peak on the Co–N SAC Mm may be related to the higher coverage of HOO* considering the similar measurement procedure of in situ ATR–SEIRAS. Summarizing the abovementioned results, we use the experimental evidence to verify the DFT calculation results that the Co–N SAC Dp with pyrrole-type CoN 4 favors the H 2 O 2 production as compared to the Co–N SAC Mm (pyridine-type CoN 4 ).…”
Section: Resultsmentioning
confidence: 78%
“…While the noble metals, especially Pt and Pd, are known to easily catalyse HER due to their lower hydrogen binding energy, the Heyrovsky and Tafel steps can be masked using transition metals or catalysts with higher hydrogen binding energy. 151 Series of non-precious metal catalysts (Cu, 149,152–155 Pb, 153 Fe, 153 Ti, 153,156,157 Ni, 153,158 ) have been tested in research for the ECH of furfural. Cu is the most widely used non-precious metal catalyst for furfural electrochemical hydrogenation and hydrogenolysis.…”
Section: Catalytic Conversion Of Biomass To Mthfmentioning
confidence: 99%
“…showed that doping or alloying additional elements into the copper surface could direct the hydrogenation of furfural to 2‐methylfuran preferentially. This surface modification and incorporation of active elements favoured the 2‐methylfuran production efficiency and also ascertained the copper catalyst stability without reaction deactivation Another work investigated the ECH of furfural to 2‐methylfuran with high faradaic efficiency using a series of bimetallic Cu−Pd catalysts and showed that the catalyst surface structure/composition plays a crucial role in determining the selectivity [30] . Dixit et al [31] .…”
Section: Introductionmentioning
confidence: 97%
“…This surface modification and incorporation of active elements favoured the 2-methylfuran production efficiency and also ascertained the copper catalyst stability without reaction deactivation Another work investigated the ECH of furfural to 2methylfuran with high faradaic efficiency using a series of bimetallic CuÀ Pd catalysts and showed that the catalyst surface structure/composition plays a crucial role in determining the selectivity. [30] Dixit et al [31] demonstrated the significance of producing bimetallic NiÀ Cu in generating higher amounts of furfuryl alcohol and hydrofuroin as compared to bulk Cu. Nevertheless, the formation of 2-methylfuran was not observed under these conditions.…”
Section: Introductionmentioning
confidence: 99%